POLA PEMBERIAN MP-ASI DAN PERTUMBUHAN PADA BAYI USIA 6-8 BULAN DI WILAYAH KERJA PUSKESMAS SIMALINGKAR MEDAN - DIAN ERVIANA; Jumirah .; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2018)
In infancy when malnutrition can cause impaired the development of the physically, mental, social, and intellectual nature of the settled and continue to be taken until the child becomes adult. The aim of this research was to know the pattern of give Complementary Feeding and growth in infants age 6-8 months in Puskesmas Simalingkar Medan region working area. Types of this research was descriptive by cross sectional design. The samples were 61 baby by total sampling methode. The primary data were obtained through interviews using food recall 24-hour and questionnaire. The result showed that an average of give Complementary Feeding has been done well, types and forms of food given to infancy age 6-8 months, which was crushed food milk or porridge and porridge filter was 41,0%, ordinary soft or food porridge and team rice was 44,2% and solid food or family meal was 14,8%. The baby growth based on weight for age (W/A) the category  normal 52,6% the category is very low 19,7%. The baby growth based on lenght for age (L/A) the category normal 37,7%, category of very sort 8,2%, the baby weight for length (W/L) category normal 47,5%, the category of very thin 8,2 %. The baby’s growth based index antropometry (W/A), (L/A), and (W/L) in this research by the outline in normal category even though the pattern of given Complementary Feeding there is still not approriate.   Key Word : Complementary feeding, growth, baby age 6-8 month